2006
DOI: 10.1111/j.0022-1112.2006.00945.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships among Thunnus species inferred from rDNA ITS1 sequence

Abstract: Intra and interspecific nucleotide sequence variation of rDNA first internal transcribed spacer (ITS1) was analysed using all eight species of the genus Thunnus plus two out-group species within the same family, skipjack tuna Katsuwonus pelamis and striped bonito Sarda orientalis. Intraspecific nucleotide sequence variation in ITS1, including intra-genomic variation, was low, ranging from 0Á003 to 0Á014 [Kimura's two parameter distance (K2P)], whereas variation between species within the genus Thunnus ranged f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 28 publications
3
50
1
Order By: Relevance
“…Some authors have hypothesized mitochondrial introgression events between different Thunnus species as the main reason for discordances between mtDNA and nuclear DNA-based inferred relationships (Chow et al, 2006;Viñas and Tudela, 2009). This is supported by our analyses as the comparative study of the COI sequences revealed two T. thynnus individuals with introgressed mitochondrial DNA (Supplementary Figure 1) that had no phylogenetic relationships with T. alalunga or T. orientalis in the nuclear DNA-based phylogenetic trees.…”
Section: Relationships Between the Atlantic And Pacific Bluefin Tunasmentioning
confidence: 99%
See 4 more Smart Citations
“…Some authors have hypothesized mitochondrial introgression events between different Thunnus species as the main reason for discordances between mtDNA and nuclear DNA-based inferred relationships (Chow et al, 2006;Viñas and Tudela, 2009). This is supported by our analyses as the comparative study of the COI sequences revealed two T. thynnus individuals with introgressed mitochondrial DNA (Supplementary Figure 1) that had no phylogenetic relationships with T. alalunga or T. orientalis in the nuclear DNA-based phylogenetic trees.…”
Section: Relationships Between the Atlantic And Pacific Bluefin Tunasmentioning
confidence: 99%
“…This is supported by our analyses as the comparative study of the COI sequences revealed two T. thynnus individuals with introgressed mitochondrial DNA (Supplementary Figure 1) that had no phylogenetic relationships with T. alalunga or T. orientalis in the nuclear DNA-based phylogenetic trees. Attending to morphological features (Gibbs Jr and Collette, 1967) and allozyme and mitochondrial molecular markers (Collette et al, 2001), the Atlantic and Pacific bluefin tunas have been considered as two different subspecies; yet, this has been questioned after their ITS1 nuclear marker sequences were found nearly identical (Chow et al, 2006). In our study, most analyses support the respective monophylies of T. thynnus and T. orientalis, with only some trees based on the smallest matrices not providing support for either of the two monophylies (Table 1).…”
Section: Relationships Between the Atlantic And Pacific Bluefin Tunasmentioning
confidence: 99%
See 3 more Smart Citations